K-Ar ages of early miocene arc-type volcanoes in Northern New Zealand - Hayward, B.W.; Black, P.M.; Smith, I.E.M.; Ballance, P.F.; Itaya, T.; Doi, M.; Takagi, M.; Bergman, S.; Adams, C.J.; Herzer, R.H.; Robertson, D.J. (Royal Society Of New Zealand, 2001)
Understanding the temporal and spatial development of the early Miocene Northland Volcanic Arc is critical to interpreting the patterns of volcanic activity in northern New Zealand through the late Cenozoic. The northwesterly trending arc is considered to have developed above a south west-dipping subduction system. The distribution of its constituent eruptive centres is described in terms of an eastern belt that extends along the eastern side of Northland and a complementary broad western belt which includes subaerial and submarine volcanic edifices. Critical examination of all 216 K-Ar ages available, including 180 previously unpublished ages, and their assessment against tectonic, lithostratigraphic, seismic stratigraphic, and biostratigraphic constraints, leads us to deduce a detailed chronology of periods of activity for the various early (and middle) Miocene arc-type volcanic complexes and centres of northern New Zealand: Waipoua Shield Volcano Complex (19-18 Ma, Altonian): Kaipara Volcanic Complex (23-16 Ma, Waitakian-Altonian); Manukau Volcanic Complex (c. 23-15.5 Ma, Waitakian-Clifdenian); North Cape Volcanic Centre (23-18 Ma, Waitakian-Altonian); Whangaroa Volcanic Complex (22.5-17.5 Ma, Waitakian-Altonian); Taurikura Volcanic Complex (22-15.5 Ma, Otaian-Clifdenian); Parahaki Dacites (22.5-18 Ma, Waitakian-Altonian); Kuaotunu Volcanic Complex (18.5-11 Ma, Altonian-Waiauan). In general, volcanic activity does not show geographic migration with time, and the western (25-15.5 Ma) and eastern (23-11 Ma) belts appear to have developed concurrently. An open access copy of this article is available from the publishers website.